DESIGN AND STATISTICAL OPTIMIZATION OF MOUTH DISSOLVING SUBLINGUAL FILM OF FIXED DOSE COMBINATION OF DOXYLAMINE SUCCINATE AND PYRIDOXINE HYDROCHLORIDE USING DESIGN OF EXPERIMENT IN THE TREATMENT OF NAUSEA AND VOMITING IN PREGNANCY - Suresh, Bobde Suwarna; Hemraj M, Tank (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present research aims at formulating a mouth dissolving sublingual film of fixed dose combination of doxylamine succinate (DS) and pyridoxine hydrochloride (PH) that would provide faster onset of action and hence relief from the condition of nausea and vomiting in pregnancy. Methods: Mouth dissolving films were prepared using a solvent casting technique. A 23 full-factorial design of eight formulations was set up with three independent variables: X1 - polymer 1 HPMC E15 concentration, X2 - polymer 2 HPMC E5 concentration, and X3 - plasticizer PEG 400 concentration. The responses, i.e., dependent variables measured for the study were Y1 disintegration time in seconds, Y2 tensile strength in kg/cm2, Y3 drug release in the percentage of DS, and Y4 drug release in the percentage of PH. All the formulations were evaluated for physicochemical parameters such as clarity, weight, thickness, folding endurance, surface pH, and content. The design expert software 11.0 trial version was used for statistical analysis of the responses. Results and Conclusion: All the film formulations were found to be transparent, non-tacky, and easily peelable having the satisfactory tensile strength and folding endurance. The concentration of polymer 1 and 2 was found to have a significant effect on disintegration time and drug release of mouth dissolving films. The best film formulation DP1 was found to have a disintegration time of 77.66 s and found to release 96.22% of DS and 95.43% of pyridoxine HCl in 21 min.